Determinación de las competencias organizacionales en la Avícola Macías del cantón Santa Ana de Manabí - Basurto Moreira, Gema María (2021)
The general objective of this research is to determine the organizational competencies for the contribution of competitive advantage in Macías Poultry, Santa Ana canton of Manabí province, it was carried out because the agroproductive sector has presented a considerable growth, where needs are created for strategically improving its organization, therefore, its implementation served to make a proposal for an action plan, which characterized the current state of the poultry, managing to define the organizational competencies with the selection of experts who contributed to the election of the most competent, based on legal, economic, social and environmental factors; to characterize the current state of the Macías poultry farm, an interview was conducted with the person in charge of the Human Talent department, who provided important information for the investigation, then the organizational competencies were defined, where according to experts the most important to study were: innovation, training and lifelong learning, biosecurity in poultry farms, communication, integrated teamwork, preservation of the environment, quality orientation, customer orientation, leadership, ethics and commitment; through the survey it was determined that seven of the competencies had flaws, for this reason an Ishikawa diagram was made with the main causesthat affect the poultry industry and in this way the action plan was proposed to be implemented in the company, with the purpose of having positive results with the optimization of resources in the competencies for employees and customers well-being.